How females perceive masculine advertising models? : Master of Business Study in Marketing at Albany Campus, Massey University, New Zealand - Xu, Yujun (Massey University, 2016)
This research helps to discover: (1) relevant masculinity types for male advertising models in China; (2) Chinese female consumers’ reaction to different masculinity types of male advertising models; (3) different characteristics of Chinese females that are relevant for reactions to different types of male advertising models in China. Based on a online survey with 384 female respondents in China, we found that Stern and Sophisticated masculinity type would be the most welcomed one among female’s view. Our results also show the importance of fashion leaders who hold totally different opinions with fashion followers. Moreover, we do not find the significant differences between different age groups, gender identity or living environment. But we confirm that fashion leaders tend to be younger, more masculinity urban female in our survey. These results should be an innovative field to the existing literature and provide implications for future male model studies. Keywords: Male masculinity types; Fashion Leadership; Stern and sophisticated; Hofstede’s cultural dimensions; Metrosexuality.
Keywords: Women consumers; Men in advertising; Male models; Body image; Male masculinity types; Fashion leadership; Stern and sophisticated; Hofstede’s cultural dimensions; Metrosexuality; China